Immune checkpoint inhibitor-related acquired amegakaryocytosis thrombocytopenia: a case report and literature review - Rivet, Valérian; Sibaud, Vincent; Dion, Jérémie; Volosov, Thibaut; Biteau, Mélanie; Pastissier, Andréa; Delavigne, Karen; Cougoul, Pierre; Rauzy, Odile; Comont, Thibault (Frontiers in Oncology, 2024)
Introduction. Immune Checkpoint Inhibitors (ICIs) are used in several advanced malignancies and may cause various immune-related Adverse Events (irAEs). Among them, hematological irAEs are less described. Acquired amegakaryocytic thrombocytopenia (AAT) is a rare immune hematologic disorder characterised by severe thrombocytopenia and complete absence of megakaryocytes in bone marrow. Case presentation. Herein, we present the case of a patient in their 40s with metastatic melanoma who developed an AAT after 12 cycles of nivolumab (anti PD1). His platelet count decreased £5´10 9 /l without other cytopenia. Bone marrow biopsy showed normal cellularity with a complete absence of megakaryocytes and T-CD8+ lymphocytes infiltration. Given the failure of systemic steroids, eltrombopag was started, an oral thrombopoietin receptor agonist (TPO-RA), and his platelet count subsequently increased with complete response. Discussion. Four others cases are described on literature with the same features than non-ICI-related-AAT. All cases occurred after anti-PD/PD-L1 treatment with a median onset of 5 weeks. Presentation of our case is quite different with delayed cytopenia. Both ciclosporin and TPO-RA seem to be efficient therapies. Conclusion. TPO-RA could be preferred in oncologic patients but safety data is still missing to define clear guidelines for immune-related-AAT management.